Next-Generation Intelligent MXene-Based Electrochemical Aptasensors for Point-of-Care Cancer Diagnostics - Parihar, Arpana; Singhal, Ayushi; Kumar, Neeraj; Khan, Raju; Khan, Mohd. Akram; Srivastava, Avanish K. (Nano-Micro Letters, 2022)
Delayed diagnosis of cancer using conventional diagnostic modalities needs to be addressed to reduce the mortality rate of cancer. Recently, 2D nanomaterial-enabled advanced biosensors have shown potential towards the early diagnosis of cancer. The high surface area, surface functional groups availability, and excellent electrical conductivity of MXene make it the 2D material of choice for the fabrication of advanced electrochemical biosensors for disease diagnostics. MXene-enabled electrochemical aptasensors have shown great promise for the detection of cancer biomarkers with a femtomolar limit of detection. Additionally, the stability, ease of synthesis, good reproducibility, and high specificity offered by MXene-enabled aptasensors hold promise to be the mainstream diagnostic approach. In this review, the design and fabrication of MXene-based electrochemical aptasensors for the detection of cancer biomarkers have been discussed. Besides, various synthetic processes and useful properties of MXenes which can be tuned and optimized easily and efficiently to fabricate sensitive biosensors have been elucidated. Further, futuristic sensing applications along with challenges will be deliberated herein. Highlights: 1 Shed light on MXene-based electrochemical aptasensors for the detection of cancer biomarkers. 2 Strategies for the design and synthesis of biomarker-specific aptamer are presented. 3 The properties such as electrical conductivity, chemical stability, mechanical properties, and the hydrophilic–hydrophobic nature of MXenes are discussed. 4 Brief insight on futuristic sensing applications along with challenges are highlighted.